Parasites of Periplaneta americana linnaeus "domestic cockroach" from Ica. - Fernádez B., Mary (2001)
244 specimens of Periplaneta americana Linnaeus from 13 localities of Ica were studied. Nematodes and protozoa were identified. They are Lophomonas blattarum, Leptomonas sp., Leidynema appendiculatum and Hammerschmidtiella diesingi. Also, parasites of man were found, three of which are pathogenic: Giardia lamblia, Blastocystis hominis and Cryptosporidium sp.